Neonatal effect of remifentanil in cesarean section with general anesthesia: A protocol of systematic review and meta-analysis - Zhang, Qi (Medicine (Baltimore), 2020)
BACKGROUND: Although several previous studies have reported the efficacy of remifentanil in cesarean section (CS) under general anesthesia, no study has specifically addressed its neonatal effect (NE) in CS under general anesthesia systematically. Thus, this study will systematically investigate the NE of remifentanil in CS under general anesthesia. METHODS: Electronic databases including MEDLINE, EMBASE, Cochrane Library, Web of Science, Chinese Biomedical Literature Database, and China National Knowledge Infrastructure will be systematically retrieved with the assistance of a specialist librarian to check randomized controlled trials reporting NE in CS under general anesthesia. We will retrieve all electronic databases from their initial time to March 20, 2020 without restrictions of language. All process of study selection, data extraction, and risk of bias evaluation will be carried out by 2 independent authors. We will invite another senior expert to solve the problems that arise between 2 authors. Data will be pooled and analyzed using RevMan V.5.3 software. RESULTS: Outcomes consist of assessment of neonatal adaptation, requirements for postoperative respiratory support of neonates, systolic and diastolic noninvasive blood pressure, mean blood pressure, heart rate, electrocardiography, umbilical cord blood gas analysis, and adverse events. CONCLUSION: This study will present evidence of the NE of remifentanil in CS under general anesthesia. This information may inform benefits of intervention to guide the usage of remifentanil in CS under general anesthesia. STUDY REGISTRATION: INPLASY202040028.